Synthesis of YBa₂Cu₄O8 superconductor and analysis of electronic properties in comparison to other YBCO family compounds - Cheong, Choon Min (2020)
In recent years, high-temperature superconductor YBCO has been recognized for developing secondary generation of coated superconductor for various technological applications due to its high transition temperature, Tc. YBa2Cu4O8 (Y124) with stoichiometric oxygen content is able to maintain Y124 phase before decomposing to YBa2Cu3O7-x (Y123) and CuO phases at temperature above 850 oC. This ascendancy of thermal stability overtook Y123 in practical applications. To date, a relatively pure YBa2Cu4O8 sample had been successfully prepared by heat treatment in high-oxygenpressure [1-4] or using wet methods [5-9] with heat treatment at ambient pressure.For YBa2Cu4O8 samples prepared by solid state reaction method at ambient pressure, either multiple grindings with repeated heat treatment [10] or usage of additional technique is required to improve the synthesis condition [11-18]. It was reported that YBa2Cu4O8 could be synthesized within hours at temperature around 1000 oC and pressure above 50 bar [1-4]. The equipment for high pressure technique is expensive and could bring about safety issues. Although the wet methods do not rely on high pressure, several processes before heat treatments is required and the sintering time is about 3-5 days with few intermittent grinding [5-9]. Solid state reaction methods offer relatively lower cost and simpler procedure as compared with the high pressure techniques and the wet methods. However, synthesis of YBa2Cu4O8 without using special treatment requires very long sintering time [10]. With the help of alkali enhancer, the sintering time of solid state reaction method is reduced to almost that of the wet methods [11,16].For YBa2Cu4O8 samples prepared by solid state reaction method at ambient pressure, either multiple grindings with repeated heat treatment [10] or usage of additional technique is required to improve the synthesis condition [11-18]. It was reported that YBa2Cu4O8 could be synthesized within hours at temperature around 1000 oC and pressure above 50 bar [1-4]. The equipment for high pressure technique is expensive and could bring about safety issues. Although the wet methods do not rely on high pressure, several processes before heat treatments is required and the sintering time is about 3-5 days with few intermittent grinding [5-9]. Solid state reaction methods offer relatively lower cost and simpler procedure as compared with the high pressure techniques and the wet methods. However, synthesis of YBa2Cu4O8 without using special treatment requires very long sintering time [10]. With the help of alkali enhancer, the sintering time of solid state reaction method is reduced to almost that of the wet methods [11,16]. Nonetheless, the sintering time and the fraction of YBa2Cu4O8 phase and impurities within the samples obtained for those solid state reaction methods are still ambiguous. Moreover, limited studies have been conducted to synthesize YBa2Cu4O8 by starting materials of YBa2Cu3O7-x and CuO [14]. On the other hand, the electronic properties of the two similar structures of Y123 and Y124 are diverse in certain situation. For example, their superconducting properties are diverse when they are doped with calcium.With calcium but suppressed the superconducting transition temperature [19-21]. On the contrary, the Tc of Y0.9Ca0.1Ba2Cu4O8 was improved to 90 K by 10.0% of calcium doped on the yttrium site [22-28]. The dependency of Tc on hole densities was observed in cuprate superconductor [29-32]. However, to determine hole densities of YBCO is non-trivial. Tallon et al. [32] used rather complicated bond-valence-sum (BVS) method to calculate the hole densities for Y123. Hence, it is urged to calculate the hole densities based on density functional theory and investigate the electronic band structure of YBCO family compound and obtain its relation to the superconducting transition temperature. This thesis was focused on the synthesis and electronic properties of Y124 phase with comparison to other YBCO family compounds. This thesis began with the study of preparation of Y124 phase by solid state reaction method with heat treatment at 1 atm oxygen pressure. X-ray diffraction technique was used to identify the phases formed and the crystal structure of Y124. Scanning electron microscope was used in order to investigate grain morphology of the samples. Thermogravimetric analysis was performed to study the thermal stability of the sample. Electrical properties of the samples were measured using the four-point probe technique. Six samples were prepared using nitrate precursors and one sample was prepared by carbonate precursor. This study was to understand the Y124 phase formation and its formation rate. From the study, it could be summarized that; Y124 phase could form if the oxide precursors underwent the heat treatment environment in favour of Y124 and the secondary oxides would persist in sample, hence clean single phase Y124 was difficult to produce. Next, starting powders tetragonal-Y123 and CuO were used to prepare Y124. Tetragonal-Y123 is obtained by heat treatment on Y123 power at 850 oC in argon gas flow for 12 hours. However, the results indicate that getting tetragonal-Y123 first is an unnecessary step. Following, Y124 was prepared directly from starting powders Y123 and CuO. By this way, significant Y124 phase was obtained after 2nd heat treatment. The lattice parameters of the synthesized Y124 were then adopted in the simulation study to analyse the electronic band structure of Y124 using density functional theory. The simulation works employed the Quantum Espresso computation package. The Y124 together with YBCO family compounds Y1236 (YBa2Cu3O6), Y12365 (YBa2Cu3O6.5), Y1237 (YBa2Cu3O7) and Ca-doped YBCO compounds YCa123 (Y0.875Ca0.125Ba2Cu3O7), YCa124 (Y0.875Ca0.125Ba2Cu4O8) were investigated. Structural optimization was obtained for all compounds using Broyden-Fletcher-Goldfarb-Shanno (BFGS) algorithm. The orthorhombicity of Y124 and Y123 compounds (Y1236, Y12365, and Y1237) agreed with the trend of Tc, where compounds with higher Tc in practice have higher orthorhombicity, however, this is not so for Ca-doped compounds. By analysing the atoms in Cu-O2 plane, Cu(2) and O(3) are moved further away from the yttrium (Y) atom for compounds with higher Tc. For Y12365 and Y1237, O(2) remained on the same level. Ca with about the same atomic radius as Y did not affect much the lattice constant and volume of the compounds. However, Ca2+ with less electronegative as compared with Y3+ modified the electronic properties of the region within the bilayers Cu-O2 plane. The calculations including band structure, density of state and charge density of the Y124 and other YBCO family compounds were then performed accordingly. The density of state at Fermi level, N(EF) and number of holes of Cu(2) and Cu-O2 showed tendency of increment consistent with the Tc of the compounds except for YCa123. Y124 with double Cu-O chains has 4.80 holes per unit cell that is higher than the Y1237 which has 3.52 holes per unit cell, but the number of holes at its Cu(2) and Cu-O2 plane are lower than the Y1237. For example, the number of holes at Cu(2) and Cu-O2 plane of Y124 are 0.60 and 1.07 respectively that is lower than Y1237 that have 0.66 holes per Cu(2) and 1.19 holes per Cu-O2 plane. Y1237 and YCa124 with Tc of around 90 K have the same number of holes in Cu(2) and Cu-O2 which are 0.66 and 1.19 respectively. The hole densities in Cu-O2 plane showed good agreement with the results of the N(EF), number of holes per Cu(2) and number of holes per Cu-O2, except for YCa124 and Y1237. Y124 and YCa124 have highest hole densities in the unit cell which are 2.33 and 2.37 respectively. However, the hole densities in Cu-O2 plane of Y124 is less than that of Y1237 which are 4.07 and 4.50 respectively. For YCa124 that has about the same Tc with Y1237, their hole densities in Cu-O2 plane is very close which are 4.56 and 4.50 respectively. In summary, the simulation studies showed that the coordinates of atoms at Cu-O2 plane and orthorhombicity could not be really related to the superconducting transition temperature of the compounds. However, the hole values on the Cu(2) atom and Cu-O2 plane did show a satisfactory relationship with the superconducting transition temperature.